2022
DOI: 10.1108/jarhe-11-2021-0413
|View full text |Cite
|
Sign up to set email alerts
|

Past-Positive time perspective predicts academic achievement via motivation, and procrastination might not be as bad as it seems

Abstract: PurposeThe present research was based on an online questionnaire. A total of 256 undergraduate psychology students aged 18–44 (M = 23.61; SD = 0.57) from the Pontifical Catholic University of Argentina took part in the study (137 women; 53.3%). A sociodemographic and academic survey and the locally adapted versions of the Zimbardo Time Perspective Inventory (ZTPI), the Motivated Strategies for Learning Questionnaire (MSLQ) and the Tuckman Procrastination Scale were used in this study. Participants were contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
1
2
0
Order By: Relevance
“…Motivation is considered a crucial factor for academic procrastination in both educational theory and practice (Zaccoletti et al, 2020), and they found that individuals tend to procrastinate more when their intrinsic motivation decreases, which is considered a type of motivation in this study. This behavior has been observed in several studies (Bagheri & Yoosefi, 2023;Bäulke & Dresel, 2023;Fernández Da Lama & Brenlla, 2023;Fridayani, 2023;Güdül et al, 2021;Serdar et al, 2021;Tisocco & Liporace, 2023). The results of the study are based on the theoretical perspective that intrinsic motivation, which fulfills basic psychological needs, reduces academic procrastination behavior .…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Motivation is considered a crucial factor for academic procrastination in both educational theory and practice (Zaccoletti et al, 2020), and they found that individuals tend to procrastinate more when their intrinsic motivation decreases, which is considered a type of motivation in this study. This behavior has been observed in several studies (Bagheri & Yoosefi, 2023;Bäulke & Dresel, 2023;Fernández Da Lama & Brenlla, 2023;Fridayani, 2023;Güdül et al, 2021;Serdar et al, 2021;Tisocco & Liporace, 2023). The results of the study are based on the theoretical perspective that intrinsic motivation, which fulfills basic psychological needs, reduces academic procrastination behavior .…”
Section: Introductionsupporting
confidence: 72%
“…At this point, Ryan and Deci (2000) define academic procrastination as a motivational problem that creates a gap between intention and action, leading to negative consequences for the individual. Many studies have shown that intrinsic motivation is effective in reducing academic procrastination and that there are negative relationships between students' intrinsic motivation and academic procrastination behavior (Abidin et al, 2023;Anwar & Qonita, 2019;Bäulke et al, 2018;Fernández Da Lama & Brenlla, 2023;Howard et al, 2021;Güdül et al, 2021;Kemal et al, 2023;Malkoç & Mutlu, 2018;Naz et al, 2021;Tisocco & Liporace, 2023;Yeşiltaş, 2020). This is because students with high motivation perceive their lessons as interesting or valuable and are less likely to persistently and irrationally procrastinate their academic tasks (Kljajic et al, 2021).…”
Section: The Relationship Between Intrinsic Motivation and Academic P...mentioning
confidence: 99%
“…There is no doubt that there is also a lack of interesting and interactive ICT-based support learning materials (Gomez et al, 2023). Numerous studies and researches highlight on the impact of online learning but less emphasis on social factors involving motivation during online classes (Abuhassna & Alnawajha, 2023;Diwakar et al, 2023;Dong et al, 2023;Fernández Da Lama & Brenlla, 2023;Fowler, n.d.;Gómez et al, 2023;Istijanto, 2023;Liu, 2023;Mannella & Tummolini, 2023;Meisner & McKenzie, 2023;Mendoza et al, 2023;Nong et al, 2023;Swain et al, 2021). Hence, this study is significant in order to seek solutions to the issues which have affected students' academic achievement in today's technology-based education.…”
Section: Background Of Studymentioning
confidence: 98%